Data Reporting as Care Infrastructure: Assembling ART Registries in Japan, Taiwan, and South Korea. Issue 1 (1st March 2020) - Wu, Chia-Ling; Ha, Jung-Ok; Tsuge, Azumi
Abstract: Collecting and reporting national data has become a routine practice for assisted reproductive technology (ART) governance. This article compares the building of national registries, the making of health statistics, and the utilization of these data in Japan, Taiwan, and South Korea. Instead of viewing data registries as tools for health surveillance or monitoring, we approach them in terms of their effectiveness in generating care . Conceptualizing ART data reporting as care infrastructure, built on Maria Puig de la Bellacasa's "matters of care, " allows us to compare the extent to which data are collected for strengthening a community's ethical obligation, presented as indicators that could reflect quality of care and inform evidence-based policy making that promotes clinical practices for healthy outcomes. We find that sociotechnical imaginaries for ART were shaped by the fact that, in its early stages, in vitro fertilization was considered controversial in Japan, a source of nationalist glory in Taiwan, and a marginal procedure in South Korea. This in turn led to different trajectories of designing national registries in these countries, resulting in different care outcomes. We also point to the importance of mediators, including reflexive medical practitioners, care-centered state bureaucrats, and activists, in translating registry data into better ART health care.